Premenstrual syndrome among budding medical professionals at medical college in a metro city: a cross sectional study - Singh, Anuradha; G. S., Triveni; Sharma, Kajal; Saran, Brijesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Premenstrual syndrome (PMS) is a group of menstrual disorder constituting various physical, emotional and behavioral symptoms occurring in the luteal phase usually a week before menstruation. It is a very common condition affecting many young girls and severity can have a negative impact on the quality of life. Our study was done to estimate the prevalence of this condition among the medical undergraduate students. Methods: This cross-sectional study was conducted at Lady Hardinge medical college, New Delhi, India among medical undergraduates after ethical clearance. A convenient sample size of 228 was taken. The participants were selected by random sampling technique and informed consent was obtained. The data was collected as per PMSS scale and analyzed by frequencies and percentages using SPSS version 21. Results: The prevalence of PMS among our enrolled participants was 100%. Majority about 61% belonged to age group of 21-25 years. About 40.8% of students had mild symptoms, 35.1% moderate, 18.0% severe and 6.1% very severe form of PMS. However, no significant difference was found in the severity between 2 age groups. Conclusions: Our study highlights 100% prevalence of PMS with varied severity of presentation. The very high prevalence of PMS among medical undergraduates calls for an urgent need to priorities the health care by creating awareness and provide necessary medical, social and psychological support to our budding professionals.